The Influence Of Interpersonal Communication On Organization Performance : A Meta-Analysis - Rahmi Wahyuni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to investigate the significant impact of interpersonal communication on overall organisational performance. This type of research is a meta-analysis research. The inclusion criteria in the study are research from national or international journals indexed by SINTA and Scopus, research related to personal communication on organisational performance, research published in 2020-2024, and attach complete data in analysing the effect size value. The analysis includes a comprehensive review of the existing literature on the topic, covering a range of industries and organisational settings. The results of the meta-analysis indicated a strong positive influence between interpersonal communication and organisational performance with a value of rES=0.818; z= 0.629; p < 0.001) with a high effect size category. Furthermore, this study revealed that effective interpersonal communication can increase employee engagement, enhance collaboration, and improve problem-solving ability, which ultimately results in better organisational outcomes. The findings also highlight the importance of considering individual differences, such as personality traits and job complexity, in understanding the impact of interpersonal communication on organisational performance. The research has significant implications for organisational leaders and managers, who emphasise the importance of fostering a culture of open and effective communication within their organisations. By understanding the critical role interpersonal communication plays in driving organisational performance, leaders can develop targeted strategies to improve communication and